2022
DOI: 10.3389/fendo.2022.895360
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA MALAT1 Aggravates Renal Tubular Injury via Activating LIN28A and the Nox4/AMPK/mTOR Signaling Axis in Diabetic Nephropathy

Abstract: BackgroundDiabetic nephropathy (DN) is a serious complication among patients with diabetes. Elucidating its pathogenesis is crucial for identifying novel biomarkers and therapeutic targets for DN.MethodsDN tissues were harvested for examining MALAT1, LIN28A and Nox4. Human kidney-2 (HK-2) cells were treated with high glucose (HG) for establishing a cell model of DN. Cell viability was examined by MTT assay. HG-induced cell apoptosis and secretion of TNF-α and IL-6 were analyzed by TUNEL and ELISA assays, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…In the current study, INO treatment signi cantly inhibited ROS levels reduced NOX4 expression. Similarly, Song et al demonstrated that ROS can accelerate the disease development of DN by treating human kidney-2 (HK-2) cells with HG to establish a cellular model of DN, knocking down NOX4 intracellularly and alleviating HG-induced cell damage by inhibiting AMPK/mTOR signaling in HK-2 cells 25 . Nrf2 is a key transcription factor that regulates oxidative stress and is capable of regulating both oxidative stress damage in type 2 DN 26,27 .…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, INO treatment signi cantly inhibited ROS levels reduced NOX4 expression. Similarly, Song et al demonstrated that ROS can accelerate the disease development of DN by treating human kidney-2 (HK-2) cells with HG to establish a cellular model of DN, knocking down NOX4 intracellularly and alleviating HG-induced cell damage by inhibiting AMPK/mTOR signaling in HK-2 cells 25 . Nrf2 is a key transcription factor that regulates oxidative stress and is capable of regulating both oxidative stress damage in type 2 DN 26,27 .…”
Section: Discussionmentioning
confidence: 99%
“…These actions would allow MALAT1 to exacerbate high glucose-induced renal tubular epithelial injury. 263 ZNF503-AS1 is a novel lncRNA with higher expression in patients with DR than in control patients. By activating TGF-β signalling, ZNF503-AS1 overexpression promotes apoptosis and suppresses proliferation.…”
Section: The Role Of Mirnas In Metabolic Diseasementioning
confidence: 99%
“…MALAT1 activated LIN28 and Nox4/AMPK/mTOR pathway, resulting in promotion of renal tubular injury in diabetic nephropathy (41). Huang et al reported that MALAT1 aggravated renal fibrosis via modulation of miR-2355-3p/IL6ST axis in diabetic nephropathy (42).…”
Section: Lncrna Malat1mentioning
confidence: 99%
“…MALAT1 activated LIN28 and Nox4/AMPK/mTOR pathway, resulting in promotion of renal tubular injury in diabetic nephropathy ( 41 ). Huang et al.…”
Section: Role Of Lncrnas In Dkdmentioning
confidence: 99%